Ganhos coletivos nas redes de cooperação intercooperativas: um estudo de caso sobre a rede Dalacto - RS - Souza, José Alves de (Universidade do Vale do Rio dos Sinos, 2012)
Organizational and economic changes of recent decades, accelerated by globalization, led to a structural realignment in the relationship between companies, workers and institutions. Facts as the increased competition and the uncertainty of the economic markets, meant that small and medium-sized enterprises lined up under a new configuration. Thus, institutions and business organizations such as the small and medium-sized enterprises (SMEs) responsive to changing market conditions, have been opted for cooperation, uniting efforts and making improvements to reduce risks and threats and seize the opportunities, becoming more competitive. In this scenario, the cooperative organizations are inserted. Similar to SMEs, they also seek better results. Both found support in the associations, around an inter-organizational network, a form of strengthening of ventures in various sectors of the economy. An example of this new venture formatting is in Rio Grande do Sul, encouraged by the Cooperation Networks Program of the State Government. In this sense, this research, through the method of qualitative research and case study, investigated the Dalacto Cooperation Network, formed by cooperatives linked to the Gaúcha Association of Dairy Ventures AGEL, located in the northwest of the State of Rio Grande do Sul. The information that underpin the research were collected through semi-structured interviews and administrative documents. From the analysis, it was possible to meet the organizational and structural formation of this Network. Its result showed that just as in the networks formed by small and medium-sized enterprises (SMEs), also in structural formation of intercooperative network, the Dalacto Network, were noticed collective gains as: a) gains of scale and power of market; b) access to solutions; c) learning and innovation; d) costs and risks reduction; and, e) social relations. This formation expresses a very important element for small producers of family farming, not only for survival, but also for the development of the dairy sector in the region.
Keywords: Redes; Cooperação em redes; Ganhos coletivos na rede; Networks; Cooperation in networks; Collective gains in the network; ACCNPQ::Ciências Humanas::Sociologia